International financial economics : corporate decisions in global markets - O'Brien, Thomas J.; O'Brien, Thomas J. (New York : Oxford University Press, 2006)
This edition explains the principles of financial economics and applies them to discussion on the motives and reasoning behind corporate finance decisions in the international marketplace.
Rev. ed. of: Global financial management. c1996.
Includes bibliographical references and index.
rua 29/06/16
Loans
Keywords: International finance; International business enterprises; Foreign exchange; Global financial management